Analysis of Paddy Price Fluctuations in the Ampara District of Sri Lanka - Ahamed, M.M. M.; Sooriyakumar, K. (University of Jaffna, 2025)
This study addresses the limited research on district-level paddy price fluctuations in Ampara, a key rice-producing region in Sri Lanka, which has been overlooked in favor of national-level analyses. It aims to analyze short- and long-term price dynamics of various paddy grain types using ARDL modelling, incorporating the effects of rice imports and inter district production. The research integrates quantitative and qualitative approaches to identify factors driving price volatility and assess its impact on farmer income and economic vulnerability. Findings will inform policy recommendations to enhance price stability and market resilience in Ampara’s paddy sector. Employing a mixed-method approach, the research combines time-series analysis using the Autoregressive Distributed Lag (ARDL) model and data collected over 22 years (2000-2022). The data includes total production in the Ampara district, annual rice import quantities for Sri Lanka, and prices of short-grain, long-grain red, and long-grain white rice. The study focuses on understanding the effects of local production levels, imports, and market dynamics on short- and long-term paddy price behavior, particularly for short-grain, long-grain white, and long-grain red rice varieties. The ARDL model reveals that rice imports and production levels negatively influence short-grain rice prices in neighboring districts, while long-grain white rice prices exert a positive influence on short-grain prices. Similarly, long-grain white and red rice prices are sensitive to both local and external production factors, reflecting broader market dynamics that affect price stability. The study highlights the significant roles of historical prices, imports, and inter-district production in shaping current price trends. The findings underscore the economic vulnerability of paddy farmers, particularly during harvest periods when price drops reduce income stability. Although government policies are aimed at price stabilization through procurement programs, they are often insufficient due to infrastructural and financial constraints.
Keywords: Ampara District; ARDL Model; Paddy; Price Fluctuations